FASILITAS PENGEMBANGAN BAHAN BAKAR HAYATI DAN EDU-REKREASI DI KAWASAN PPS NIZAM ZACHMAN JAKARTA UTARA - Patricia Clariesta; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2026)
Abstract The Samudera Nizam Zachman Oceanic Fishing Port (PPS) in Muara Baru, North Jakarta, is one of the largest fishing ports in Indonesia, supporting marine industrial activities on a national scale. The high intensity of fish landing, auctioning, and seafood processing activities, combined with organic waste generated from dense residential areas and surrounding supporting activities, produces large volumes of fish residues and food waste that remain inadequately managed. This condition has led to the degradation of coastal environmental quality and reflects a low level of public awareness regarding the importance of organic waste management as a reusable resource. This study aims to design a facility that integrates industrial functions for organic waste processing with edu-recreational functions, combining educational and recreational activities that allow the public to understand and directly observe waste processing processes, as well as commercial functions to support the local economy. The research adopts a qualitative–descriptive method, including a literature review, field observations to map industrial activities and sources of organic waste from both the port area and surrounding residential settlements, spatial analysis to identify relationships between industrial and public zones, and comparative studies of relevant industrial–public facilities. The design process is conducted through stages of analysis, synthesis, and transformation using Bernard Tschumi’s transprogramming approach, which enables interactions between production spaces and public spaces. The design outcomes indicate that the proposed facility has the potential to serve as a model for organic waste processing and bioenergy production that is adaptive to the socio-ecological context of fishing areas, while also functioning as a medium for environmental education and coastal regeneration. Keywords: Biofuel; fishing port; organic waste processing; regenerative architecture; transprogramming Abstrak Kawasan Pelabuhan Perikanan Samudera (PPS) Nizam Zachman di Muara Baru, Jakarta Utara, merupakan salah satu pelabuhan perikanan terbesar di Indonesia yang menopang aktivitas industri laut berskala nasional. Tingginya intensitas kegiatan pendaratan, pelelangan, dan pengolahan hasil laut, ditambah limbah organik dari permukiman padat dan aktivitas pendukung di sekitarnya, menghasilkan volume sisa ikan dan sampah makanan dalam jumlah besar yang belum tertangani secara optimal. Kondisi ini memicu penurunan kualitas lingkungan pesisir dan memperlihatkan rendahnya kesadaran masyarakat terhadap pentingnya pengelolaan limbah organik sebagai sumber daya yang dapat dimanfaatkan kembali. Penelitian ini bertujuan merancang fasilitas yang mengintegrasikan fungsi industri pengolahan limbah organik dengan fungsi edu-rekreasi, yaitu gabungan fungsi edukatif dan rekreatif yang memungkinkan masyarakat memahami dan melihat langsung proses pengolahan limbah, serta fungsi komersial untuk mendukung ekonomi lokal. Metode penelitian yang digunakan bersifat kualitatif – deskriptif, meliputi studi literatur, observasi lapangan untuk memetakan aktivitas industri dan sumber limbah organik dari kawasan pelabuhan dan permukiman, analisis spasial untuk mengidentifikasi hubungan antara zona industri dan publik, serta studi komparatif terhadap fasilitas industri-publik yang relevan. Tahap perancangan dilakukan melalui proses analisis, sintesis, dan transformasi menggunakan pendekatan transprogramming Bernard Tschumi yang memungkinkan terciptanya interaksi antara ruang produksi dan ruang publik. Hasil perancangan menunjukkan bahwa fasilitas ini berpotensi menjadi model pengolahan limbah organik dan produksi energi hayati yang adaptif terhadap konteks sosial-ekologis kawasan perikanan, sekaligus berperan sebagai medium edukasi dan regenerasi lingkungan pesisir.